Advances in Multimedia Modeling 18th International Conference, MMM 2012, Klagenfurt, Austria, January 4-6, 2012. Proceedings - Schoeffmann, Klaus; Merialdo, Bernard; Hauptmann, Alexander G.; Ngo, Chong-Wah.; Andreopoulos, Yiannis; Breiteneder, Christian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 18th International Multimedia Modeling Conference, MMM 2012, held in Klagenfurt, Austria, in January 2012. The 38 revised regular papers, 12 special session papers, 15 poster session papers, and 6 demo session papers were carefully reviewed and selected from 142 submissions. The papers are organized in the following topical sections: annotation, annotation and interactive multimedia applications, event and activity, mining and mobile multimedia applications, search, summarization and visualization, visualization and advanced multimedia systems, and the special sessions: interactive and immersive entertainment and communication, multimedia preservation: how to ensure multimedia access over time, multi-modal and cross-modal search, and video surveillance.
Keywords: Computer science; Database management; Information storage and retrieval; Multimedia information systems; Image processing; Pattern recognition; Computer Science; Multimedia Information Systems; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Pattern Recognition; Database Management; Image Processing and Computer Vision; Electronic books